Designing a collaborative virtual conference application: challenges, requirements and guidelines - Teo, Rhun Ming; Mohd Norowi, Noris; Wirza, Rahmita; Kamaruddin, Azrina (Multidisciplinary Digital Publishing Institute, 2021)
Due to the recent COVID-19 pandemic that has swept the globe, more people are working from home. People use synchronous applications to communicate remotely because they are not able to meet face-to-face. However, few research studies on the issues surrounding the virtual conference application, particularly those that include collaborative activities, have been conducted. The usability study recruited 16 participants (in four groups of four) to communicate synchronously while performing collaborative activities, such as drawing together on a shared screen. According to the findings of the usability study, users do not often use the collaborative tools provided by the current virtual conference application. This is due to low exposure and unfamiliarity with the use of collaborative tools. The findings also show that users frequently do not turn on the web camera due to several reasons, including privacy, connectivity issues, the environment, and background distraction. Turning on the web camera can also cause anxiety due to shyness in front of the camera. However, some participants prefer to turn on the web camera so that they can see each other’s reactions when performing collaborative activities. The article provides several guidelines to assist in the design of virtual conference applications, including a simple familiar intuitive interface to encourage the use of collaborative tools and also introduces the use of virtual avatars as a way to represent oneself during online meetings to allow affective sharing while respecting the privacy of its users.